Unsteady Aerodynamics of Flapping Wing of a Bird - M. Agoes Moelyadi; Hendra Adi Putra; Gottfried Sachs (Journal of Engineering and Technological Sciences, 2013)
The unsteady flow behavior and time-dependent aerodynamic characteristics of the flapping motion of a bird's wing were investigated using a computational method. During flapping, aerodynamic interactions between bird wing surfaces and surrounding flow may occur, generating local time-dependent flow changes in the flow field and aerodynamic load of birds. To study the effect of flapping speed on unsteady aerodynamic load, two kinds of computational simulations were carried out, namely a quasi-steady and an unsteady simulation. To mimic the movement of the down-stroke and the upstroke of a bird, the flapping path accorded to a sinus function, with the wing attitude changing in dihedral angle and time. The computations of time-dependent viscous flow were based on the solution of the Reynolds Averaged Navier-Stokes equations by applying the k-e turbulence model. In addition, the discretization for the computational domain around the model used multi-block structured grid to provide more accuracy in capturing viscous flow, especially in the vicinity of the wing and body surfaces, to obtain a proper wing-body geometry model. For this research, the seagull bird was chosen, which has high aspect ratio wings with pointed wing-tips and a high camber wing section. The results include mesh movement, velocity contours as well as aerodynamic coefficients of the flapping motion of the bird at various flapping frequencies.